Behavioral science in the global arena. volume 1 : addressing timely issues at the United Nations and beyond - Congress, Elaine Piller; Takooshian, Harold; Asper, Abigail (Behavioral science in the global arena ;, 2020)
Behavioral scientists are increasingly involved in international work through cross cultural research, conference presentations, and faculty exchanges. Psychology and social work NGOs work at the United Nations, both on providing professional consultation on timely issues, as well as advocating to promote human rights and sustainable development. Although this work at the United Nations is an important arena for behavioral scientists, this has been barely covered in the academic literature.'What are growing roles of psychology and the behavioral sciences at the United Nations today?' This first-ever volume brings together over 20 authors--both key experts and student interns--to answer this question. As the United Nations pursues its 17 Sustainable Development Goals (SDGs) for the year 2030, behavioral scientists now occupy increasingly diverse roles to pursue evidence-based answers for these 17 timely SDGs.This panoramic yet concise 230-page volume is designed for students and professionals in the behavioral sciences, psychology and social work to provide state-of-the-art information on how behavioral scientists are addressing diverse global issues today. Each chapter offers a concise overview of a topic, including a glossary of current concepts, and citations to current research.